Personality, Intelligence, and Second Language Learning Success: A Systematic Review - Wei Xu (Behavioral Sciences)
This paper discusses the interrelation between personality and intelligence in acquiring a second language (L2). From 13 studies and the available literature, it determines that extraversion, openness, and conscientiousness, as well as subdomains of emotional intelligence (well-being, empathy, and sociability) are important in predicting L2 motivation, perseverance, and achievement. The interpretation also outlines L2-specific trait emotional intelligence (TEI) and cultural intelligence as the key factors explaining why learning may be consistent with various measures other than general variables. Furthermore, it elaborates on how self-control, perseverance, and mindset assist in coping with language learning anxiety and promoting greater engagement with language learning. However, there are some limitations to this study, focusing on cross-sectional data and the homogeneity of the learner population. Therefore, follow-up work should take into account a longitudinal approach, examine the role of IPAs in learning L2, and move towards integrative perspectives in which the dispersive connections between traits of personality and intelligence and L2 proficiency would be adequately captured.